EFFECTIVENESS REGULATION MINISTER OF MARITIME AFFAIRS AND FISHERIES NO. 71/2016 TO FISHING GEAR FISHERMAN OF CANOE BAGAN AT BUNGUS OCEAN FISHING PORT OF WEST SUMATERA - Dian Triana; Hendrik Hendrik; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research is about effectiveness regulation minister of maritime affairs and fisheries at Bungus Ocean Fishing Port has been done in April 2018. The purpose of this research is to find out implementation of the effectiveness of Permen-KP No 71 of the year 2016 in PPS Bungus and knowing the problems that arise regarding the effectiviness of Permen-KP No 71 of the year 2016.The research method used is the method of the survey with the approach of a qualitative, that is conducting observations directly to the field.The determination of respondents technique be used Purposive Sampling with a total of 18 respondents.The research showed that Permen-KP no 71 of the year 2016 on the chart it’s still not effective due to lack of socialization to fishermen regarding the use of the fishing who environmentaly friendly. The application of the Permen-KP No 71 of the year 2016 in PPS Bungus there are pros and cons in the community. The problem in dealing with the application of Permen KP No 71 of the year 2016 againts the use of lights, the nets and the arrest on a chart also have an impact with the advent of fear of a fisherman when fishing, the reduced by fishermen, the number of fishermen who are unemployed, and the difficulty of fishermen to move to the arrest. Keywords: Effectiveness, MoMA&F Regulation, The arrest of the chart